ChemInform Abstract: An Efficient One‐Pot Synthesis of 3, 5‐Diaryl‐4‐bromopyrazoles by 1, 3‐Dipolar Cycloaddition of in situ Generated Diazo Compounds and 1‐Bromoalk‐1‐ynes. Issue 21 (2nd May 2013) - Sha, Qiang; Wei, Yunyang
Abstract Aldehyde‐derived hydrazones produce isomerization products of type (III)/(V), whereas ketone‐derived hydrazones afford cycloadducts such as (VII), (IX) or (XI).